Thin films of poly(vinylidene fluoride-: Co -hexafluoropropylene)-ionic liquid mixtures as amperometric gas sensing materials for oxygen and ammonia - Lee, Juni; Hussain, Ghulam; López-Salas, N.; Macfarlane, D.R.; Silvester-Dean, Debbie (ROYAL SOC CHEMISTRY, 2020)
© The Royal Society of Chemistry 2020.